Aquaculture research techniques in Nigeria: opportunities and challenges for sustainable aquaculture development - Ekemini M. Okon; Babatunde T. Adesina; Babatunde M. Falana; Judith O. Ehigie; Adeniran M. Bolanle; Reuben C. Okocha (Scientific African)
Nigeria has great potential for aquaculture production, but has yet to match domestic demand sustainably. Generally, the challenges are due to weak aquaculture governance, including incoherent planning and inadequate finance for advanced research. It is, therefore, necessary to seek advanced knowledge-based strategies and plans to promote aquaculture in the country. Such strategies and plans may require developing a database that assesses current aquaculture research techniques to appraise past and current scientific publications, from which a direction can be mapped for future research. Despite its importance, no study has assessed the various techniques employed across different aspects of aquaculture research in Nigeria. Hence, the present study compares the research techniques employed in Nigeria with those used in other top aquaculture-producing countries. Some of the techniques used for aquaculture research in Nigeria differ from those in other top aquaculture-producing countries, which can impact the innovative outcomes in aquaculture development in Nigeria. Specifically, leading countries typically employ high-throughput methods, such as omics, machine learning, and real-time environmental monitoring, whereas Nigerian research primarily relies on traditional laboratory techniques. This technological gap slows innovation and limits the scalability of results. These differences emphasize the need to adopt internationally validated methods to increase aquaculture productivity in Nigeria. While advanced techniques in top aquaculture-producing nations may lead to increased efficiency and higher yields, Nigeria's unique approaches can foster innovation tailored to local conditions and resource constraints. A SWOT analysis revealed government interest in aquaculture as a strength, among others. Weaknesses included unstable policies and poorly implemented frameworks. Opportunities included the government's prioritization of aquaculture industry development, while threats included the impact of climate change, among others. Future research in Nigeria should integrate advanced techniques for aquaculture, such as those utilized in advanced aquaculture-producing nations. These countries have invested substantially in aquaculture technologies, improving production, sector growth, and development. By adopting these strategies and techniques, Nigeria has the potential to boost its aquaculture sector and ultimately advance its development.